Broiler breeder feeding programs and trace minerals on maternal antibody transfer and broiler humoral immune response - Oviedo-Rondón, E. O.; Leandro, N. M.; Ali, R.; Koci, M.; Moraes, V. [UNESP]; Brake, J. (My University, 2013)
Breeder feed restriction may negatively affect broiler progeny immunity. Sources of trace minerals (TM) with higher bioavailability in breeder diets have been reported to enhance humoral and cellular immunity in broiler progeny. An experiment was conducted to examine the effects of breeder feeding programs and TM dietary sources on maternal antibody transfer and humoral immune response of progeny to a live vaccine against Newcastle disease virus (NDV). Cobb 500 breeders were fed according to 2 feed allocation programs, sigmoid late fast and sigmoid late slow, from 14 to 29 wk of age. From 56 to 62 wk of age, breeders were fed with either inorganic TM or an organic source (OTM) to replace 30% of Cu, Zn, and Mn. Progeny broilers were vaccinated intraocularly with La Sota NDV vaccine at 7 d of age. Blood samples were collected at hatching, 4, and 14 d postvaccination. Serum antibody levels against NDV were assessed by ELISA and cytokine expression by real time PCR. At hatching, late slow breeder progeny fed diets with 30% OTM had higher antibody titers as compared with progeny of breeders fed 100% inorganic TM. Similar results were observed 2 wk postvaccination. Breeder feeding programs and TM sources affected the expression level of IL-4 in NDV vaccinated broiler progeny. It was concluded that breeder feeding programs influenced humoral immune response to NDV vaccine in the broiler progeny, and 30% OTM may increase these responses. © 2013 Poultry Science Association, Inc.
Keywords: Breeder; Broiler; Feeding program; Immunology; Organic mineral